An iterative ITI cancellation method for multi-head multi-track bit-patterned magnetic recording systems - Santi Koonkarnkhai; Piya Kovintavewat (Digital Communications and Networks, 2021)
Bit-Patterned Magnetic Recording (BPMR) is one of the emerging data storage technologies, which promises an Areal Density (AD) of about 4 Tb/in2. However, a major problem practically encountered in a BPMR system is Inter-Track Interference (ITI) that can deteriorate the overall system performance, especially at high ADs. This paper proposes an iterative ITI cancellation method for an m-head m-track BPMR system, which uses m heads to read m adjacent tracks and decodes them simultaneously. To cancel the ITI, we subtract the weighted readback signals of adjacent tracks, acting as the ITI signals, from the readback signal of the target track, before passing the refined readback signal to a turbo decoder. Then, the decoded data will be employed to reconstruct the ITI signal for the next turbo iteration. Experimental results indicate that the proposed system performs better than the conventional system that uses one head to read one data track. Furthermore, we also find out that the proposed system is more robust to media noise and track misregistration than the conventional system.